Low-Voltage Area at the Anterior Wall of the Left Atrium Is Associated With Thromboembolism in Atrial Fibrillation Patients With a Low CHA2DS2-VA Score - Ding, Xiangwei; Li, Mingfang; Chen, Hongwu; Yang, Gang; Zhang, Fengxiang; Ju, Weizhu; Gu, Kai; Li, Jianqing; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
Background Nonvalvular atrial fibrillation (NVAF) in patients at low risk of thromboembolism (TE) does not mean “no risk”. We sought to assess the risk factors associated with TE in clinically low-risk AF patients with a non-gender CHA2DS2-VASc score (CHA2DS2-VA score) of 0 or 1. Methods In this single-center cross-sectional study, NVAF patients with a CHA2D-VA score of 0 or 1 who underwent index high-density bipolar voltage mapping of the left atrium (LA) and AF ablation were consecutively enrolled from 2017 to 2020. The population was divided into patients with and without TE history before voltage mapping. AF patients with CHA2DS2-VA score of 0 to 1 before TE (TE group) were analyzed and compared with clinically low-risk AF patients without TE history (non-TE group). The association among LA low voltage area (LVA), other clinical factors and TE history was analyzed with logistic regression. Results In the TE group, LVA was more prevalent (15/25 [60%] vs. 105/359 [29.2%], p=0.003) and more preferentially located at the anterior wall (8/15 [53%] vs. 24/105 [23%], p=0.025). Among patients with LVA, the activation time from the sinus node to the left atrial appendage was significantly longer in the TE group (77.09±21.09 ms vs. 57.59±15.19 ms, p <0.001). Multivariate analysis demonstrated that LVA at the anterior wall of the LA (OR: 4.17 [95% CI: 1.51 to 11.51]; p=0.006) and being female (OR: 3.40 [95% CI: 1.36 to 8.51]; p=0.009) were associated with TE history. Conclusions LVA at the anterior wall of the LA is associated with TE history in NVAF patients with a low CHA2DS2-VA score.